Developing Arabic Curriculum of Kuliyatul-Mu’allimin Al-Islamiyah Raudhotus Salaam Yogyakarta - Jenur, Muhammad Khafid; Setiyawan, Agung (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
This study aims to describe the problems of the KMI curriculum development at the Raudhotus Salaam Islamic Boarding School, Yogyakarta, including planning, implementation, and evaluation—research using descriptive qualitative. Data collection techniques use observation, interview, and documentation. The informants in this study were school principals, the curriculum department, and one teacher. The result. The teachers and staff of KMI experience difficulties implementing the KMI curriculum in Arabic language learning because they are still adapting to both the Ministry of Education's and KMI curricula. The implications of the KMI curriculum are very suitable because it can increase the potential to learn Arabic.